2021
DOI: 10.7554/elife.65906
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting cortico-cerebellar communication impairs dexterity

Abstract: To control reaching, the nervous system must generate large changes in muscle activation to drive the limb toward the target, and must also make smaller adjustments for precise and accurate behavior. Motor cortex controls the arm through projections to diverse targets across the central nervous system, but it has been challenging to identify the roles of cortical projections to specific targets. Here, we selectively disrupt cortico-cerebellar communication in the mouse by optogenetically stimulating the pontin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 56 publications
4
67
0
Order By: Relevance
“…For example, it has often been proposed that dexterity demands could be intimately tied to the function of corticopontine PT pathways ( 4 ), and yet, inactivation of dSTR also profoundly impairs movement amplitude during reach-to-grasp tasks ( 21 ) as it does for joystick movements ( 22 ), perhaps consistent with a role for corticostriatal IT neurons. Moreover, inactivation of the basal pons produces little effect on movement speed and amplitude ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has often been proposed that dexterity demands could be intimately tied to the function of corticopontine PT pathways ( 4 ), and yet, inactivation of dSTR also profoundly impairs movement amplitude during reach-to-grasp tasks ( 21 ) as it does for joystick movements ( 22 ), perhaps consistent with a role for corticostriatal IT neurons. Moreover, inactivation of the basal pons produces little effect on movement speed and amplitude ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, it has often been proposed that dexterity demands could be intimately tied to the function of corticopontine PT pathways ( 4 ) and yet inactivation of dorsal striatum also profoundly impairs movement amplitude during reach-to-grasp tasks ( 21 ) as it does for joystick movements ( 22 ) perhaps consistent with a role for corticostriatal IT neurons. Moreover, inactivation of the basal pons produces little effect on movement speed and amplitude ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…The circuit regulating voluntary movements was first described as the cerebro-cerebellar pathway (Brodal, 2010 ). However, several recent studies have shown how other brain regions, such as the pontine nuclei and the ventrolateral nuclei of the thalamus (VL), also retain an active role in the regulation of distinct voluntary movements (Schwarz and Thier, 1999 ; Bosch-Bouju et al, 2013 ; Guo et al, 2021 ). This network connects the cerebral neocortex to the cerebellum via the pontine nuclei and vice versa the cerebellum to the neocortex through the VL nucleus of the thalamus.…”
Section: Nr2f1 -Dependent Development Of the Sensorimotor Systemmentioning
confidence: 99%
“…Further, a recent study assessing the role of pontine nuclei in voluntary movements supports their direct involvement in the timing and accuracy of movements rather than its initiation. Specifically, upon optogenetic disruption of the pontine nuclei activity, the animals retained the ability to initiate the reaching phase of the single-pellet task but showed either reduced precision of the grasping phase or a general delay in the complete execution of the task (Guo et al, 2021 ). Since the defects showed by Nr2f1 cortical cKO mice resemble those presented in this work, with an almost intact reaching phase but inaccurate grasping (Tomassy et al, 2010 ), it is tempting to speculate that gradient cortical Nr2f1 expression could impart topographic information to descending tracts during development by influencing their connectivity to subcortical structures, such as the pontine nuclei and the spinal cord.…”
Section: Nr2f1 -Dependent Development Of the Sensorimotor Systemmentioning
confidence: 99%